2007
DOI: 10.1038/sj.eye.6702920
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the association between 677C>T and 1298A>C 5,10-methylenetetra- hydrofolate reductase gene polymorphisms and normal-tension glaucoma

Abstract: Purpose Homozygous polymorphism of the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene and resultant hyperhomocysteinaemia have been established as an independent risk factor for vascular diseases. There are evidences that vascular abnormalities are involved in the pathogenesis and progression of normaltension glaucoma (NTG). In the present study, we were to find out the associations between 677C4T and 1298A4C polymorphisms of the MTHFR gene and NTG. Methods This was a retrospective, casecontrolled study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
2
7
2
Order By: Relevance
“…A Swedish study involving a relatively larger sample size than ours also reported lack of association between MTHFR C677T and POAG [18]. Similar lack of association was also obtained in populations from Iowa (U.S.A.) and Korea [19], [20].…”
Section: Discussionsupporting
confidence: 86%
“…A Swedish study involving a relatively larger sample size than ours also reported lack of association between MTHFR C677T and POAG [18]. Similar lack of association was also obtained in populations from Iowa (U.S.A.) and Korea [19], [20].…”
Section: Discussionsupporting
confidence: 86%
“…Through analysis of indigenous tribes of Costa Rica, Herrmann et al (2004) found that the 677T allele was present in 69% of the population, the current highest observed prevalence of this polymorphism in the world. The high frequency of this polymorphism in the Asian countries Japan (40%) and Korea (44%) (Matsuo et al, 2004;Woo et al, 2009) were significantly different from the frequency found in this study (P = 0.003 and P = 0.011, respectively). Among the Arab countries, the frequency of this polymorphism ranges from 7 to 31% (Almawi et al, 2005;Hussein, 2012).…”
Section: Discussioncontrasting
confidence: 46%
“…22 However, this association with POAG has not yet been replicated in other studies, including three studies of Caucasians [63][64][65] and two of Asians, 66,67 although one study of Koreans suggested a possible association with younger NTG. 68 In the present study, we did not find any association between this SNP and POAG in the Chinese.…”
Section: Discussioncontrasting
confidence: 46%